STUDY ON INTERPERSONAL MEANING REPRESENTATION IN AN ENGLISH INTERACTION - Sunardi Sunardi (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2009)
This spoken discourse analysis adopted the model of casual conversation analysis as suggested by Eggins and Slade (1997).The corpus of data of this study was a taped English casualconversation between a non-native speaker (NNS) and a native speaker (NS). The transcribed conversation was analyzed to know the mood patterns and the speech function patterns of the interactants. The mood patterns were studied from the types of clause structures chosen by the interactants, while the speech function patterns were studied through the choice of speech functions when the interactants acted on each other. The interpersonal relationships between the interactants wereinterpreted from the synoptic quantification of the mood and speech function patterns. The study revealed that NNS was the dominant interactant and played his role as initiator, while NS is the marginal interactant and played her role as supporter; the conversation was the one of information negotiation rather than goods and services negotiation signed by the dominant production of declaratives by both NNS and NS; and NNS favoured on negotiating opinion information, while NS prefered factual information negotiation.. It is suggested that casual conversation needs to be considered in designing syllabus to complement the current practices of conversation which focus on pragmatic conversation; authentic text, such as casual conversation, needs to be used in language classroom to avoid genre shock in students’ daily activities; and speech functions and their lexicogrammatical realizations need to be introduced to students to enrich them with possible moves in sustaining a conversation.Key words: English interaction , interpersonal meaning, representation